Qaboosism in Historical Perspective: British Policy, Rule Legitimacy and Resistance in Oman - Fazari, Mohammed al- (Springer Nature Switzerland, 2026)
Keywords: Vie politique – Oman – 1970-2020

Oman – Islamists and the “Omani Spring” - Hashimi, Said Sultan Al (Islamists and the Arab Revolutions: Bitter Experiences, 2025)
This chapter sheds light on the engagement of Islamists in Oman before, during, and after the Arab and Omani uprising, addressing the under-researched nature of
Keywords: Vie politique – Oman – 1970-2020

نهج السلطان قابوس في احتواء وتحييد النفوذ القبلي فس سلطنة عمان - الخروصية, شيخة بنت عمر (دراسات عربية في التربية وعلم النفس, 2025)
Keywords: Vie politique – Oman – 1970-2020

Oman 1974 - 2022/23 - Axon, Anthony; Hewitt, Susan (Brill, 2025)
The seventh in the CAIW series, this title draws on the 50 years of experience of Cambridge based World of Information. During most of the period covered, Oman was ruled by Sultan Qaboos bin Said, overcoming several handicaps, including modest hydrocarbon revenues, and during the first years of Qaboos’ reign, a rebellion in the southern province of Dhofar. The latter was often described as a full-blown war with the neighbouring People’s Democratic Republic of the Yemen (PDRY) and its Soviet supporters. Nevertheless, this strategically located, mostly Ibadhi sect Sultanate, has developed from a medieval, into a modern state.
Keywords: Politique étrangère – Oman – 1970-2020; Sources – Oman; Vie politique – Oman – 1970-2020

Britain and Oman, c. 1945–1980: The Silent Relationship - Bradshaw, Tancred (Springer Nature Switzerland, 2025)
Keywords: Dhofar; Relations – Oman – Royaume-Uni; Vie politique – Oman – 1932-1970; Vie politique – Oman – 1970-2020

The Dhofar War : British Covert Campaigning in Arabia 1965-1975 - Quick, Stephen (University of Exeter Press, 2025)
Keywords: Dhofar; Vie politique – Oman – 1970-2020

عمان حضارة عريقة: دولة حديثة نحو اقتصاد مبني على المعرفة والخدمات - McBrierty, Vincent; بن الزبير, محمد (مؤسسة بيت الزبير, 2004)
OCLC: 1201761651
Keywords: Vie politique – Oman – 1970-2020

The Dhofar Revolution: An Archival Analysis of the Conflict (1965-1976) - Albedwawi, Saif (Journal of Islamic Thought and Civilization, 2024)
Britain's military presence in the Middle East underwent a significant transformation by the 1960s, characterized by contractions to establish smaller bases in Aden and the Gulf; however, the British military marked a significant change in contrast to its former stronghold at the Suez base. These bases protected vital oil interests and fulfilled Britain's obligations to local rulers. However, political developments within the Gulf and the Arabian Peninsula increasingly challenged Britain's strategic position. These evolving dynamics necessitated a re-evaluation of both diplomatic and military strategies leading to the most far-reaching anti-British revolution, the Dhofar Revolution in Oman. The scholarly discourses concerning the end of the revolution have highlighted the reintegration of the Dhofar society that was actively engaged in the revolutionary struggles of broader Omni society. Nevertheless, the mechanisms employed for their success/failures have not been covered in the existing literature. Consequently, this paper aims to fill this existing gap in the literature by contextually analysing the present literature and archival documents on the Dhofar war. For this purpose, the authors extensively utilized archival documents available within the Arabian Gulf Digital Archive (AGDA) in Abu Dhabi. Moreover, the Dhofari rebel literature derived from The Gulf Bulletin fervently promoted the communist revolutionary ideology. On the other hand, the Omani government's viewpoint was extensively disseminated through its military propaganda branch, aiming to counter the rebels' influence. This paper posits that, despite the strong support from the Communist bloc, the Dhofari Revolution ultimately failed because the rebels made hastened attempts to replace the region's traditional cultural values and Islamic beliefs with their novel ideological vision. This alienated the Dhofari population, causing the rebels to lose the support of the people they aspired to lead.
Number: 2
Keywords: Dhofar; Vie politique – Oman – 1932-1970; Vie politique – Oman – 1970-2020

Democratic Refusal: Silent Citizenship in Oman - Tersmette, Keye Simon (2024)
Keywords: Vie politique – Oman – 1970-2020

Constructing Oman’s Peaceful Identity: Alignment Strategies and Discursive Identifications Under Sultan Qaboos bin Said - Daga, Giulia (Springer Nature Switzerland, 2024)
This book offers a comprehensive and insightful exploration of Oman’s discourses on foreign policy and national identity in the context of the Middle East. The Sultanate of Oman is often hailed as a peaceful exception in the region, but this work goes beyond surface-level observations to reveal the intricate complexities of Oman’s foreign policy and identity construction. With a keen focus on deconstructing essentialist understandings, the chapters delve into how discursive alignments and identity contents have shaped the government’s quest for legitimacy, recognition, and status. Employing a pioneering discourse historical approach to compare the National Day speeches and UN General Assembly speeches throughout Sultan Qaboos bin Said Al Bu Saidi’s reign (1970–2020), the author reveals how discourse evolved based on time, issues, and audiences. Notably, the book situates Oman within the context of the Gulf Cooperation Council states, examining how the Omani government’s interlinked discourses on identity and foreign policy contributed to differentiate the Sultanate from other Gulf countries. With chapters exploring Oman’s foreign policy principles, its material and ideological response to the ideas linked to the Dhofar Revolution, and its interactions with the Arab world and the international community, readers of this book will gain a comprehensive understanding of Oman’s evolving national and supranational identifications and the dynamic nature of its foreign policy. Challenging prevailing narratives while providing a fresh perspective on the relations between Oman’s foreign policy and identity construction, this book marks an important text for scholars as well as policymakers and anyone interested in understanding the intricate dynamics of Oman’s role in the global stage.
Keywords: Vie politique – Oman – 1970-2020

الضمانات الدستورية لاستقلال السلطة التشريعية في سلطنة عمان - الشوابكة, محمد عبد االله (مجلة المستقبل للدراسات القانونیة و السیاسیة, 2024)
Keywords: Vie politique – Oman – 1970-2020

Contemporary Oman: The Sultan, the People and the Stability - Zweiri, Mahjoob; Qawasmi, Farah Al (Gerlach Press, 2024)
At a time of rapid international change and marked regional dynamism, the Sultanate of Oman is emerging as a nation of surprising significance. Oman is a unique case of a Gulf state strategically and culturally located at a crossroads between the Indian Ocean, the Arabian Sea and the Persian Gulf. From this position, the Sultanate has developed its own political identity and pursued a unique foreign policy in the turbulent Middle East region, enabling the country to survive and overcome the challenges of the region. Over the years, the Sultanate has earned the title "Switzerland of the Middle East" due to its political neutrality and its prominent role as a regional mediator and peacekeeper. Renowned local and international authors as well as promising younger scholars present studies on the history, politics, economy and culture of Oman.
Keywords: Vie politique – Oman – 1970-2020

La femme omanaise au Conseil d'Etat: une participation efficiente dans le processus de développement - Sassine, Georges (La femme omanaise sur le chemin de la parité, 2019)
Keywords: Vie politique – Oman – 1970-2020

La femme dans les instances dirigeantes du Sultanat, au parlement et dans les conseils municipaux - Kharusi, Sultan al-; Kharusi, Safaa al- (La femme omanaise sur le chemin de la parité, 2019)
Keywords: Vie politique – Oman – 1970-2020

La condition de la femme à Oman: faits et chiffres - Sassine, Georges (La femme omanaise sur le chemin de la parité, 2019)
Keywords: Vie politique – Oman – 1970-2020

La femme dans les lois omanaises - Sassine, Georges (La femme omanaise sur le chemin de la parité, 2019)
Keywords: Vie politique – Oman – 1970-2020

Ces femmes qui ont marqué l'histoire d'Oman - Sassine, Georges (La femme omanaise sur le chemin de la parité, 2019)
Keywords: Vie politique – Oman – 1970-2020

Le rôle des femmes dans les différents métiers et professions - Sassine, Georges (La femme omanaise sur le chemin de la parité, 2019)
Keywords: Vie politique – Oman – 1970-2020

Oman: les femmes pionnières - Sassine, Georges (La femme omanaise sur le chemin de la parité, 2019)
Keywords: Vie politique – Oman – 1970-2020

La femme omanaise dans le sens de l'histoire - Conway-Mouret, Hélène (La femme omanaise sur le chemin de la parité, 2019)
Keywords: Vie politique – Oman – 1970-2020

La femme omanaise entre héritage et modernité - Zibaoui, Orass (La femme omanaise sur le chemin de la parité, 2019)
Keywords: Vie politique – Oman – 1970-2020

Oman : une expérience migratoire et brassage de cultures - Sharji, Safia Mohamed al- (La femme omanaise sur le chemin de la parité, 2019)
Keywords: Vie politique – Oman – 1970-2020

La femme dans le processus omanais de développement - Lawati, Suad al- (La femme omanaise sur le chemin de la parité, 2019)
Keywords: Vie politique – Oman – 1970-2020

L'égalité est un tournant sociétal progressif - Médevielle, Pierre (La femme omanaise sur le chemin de la parité, 2019)
Keywords: Vie politique – Oman – 1970-2020

Il y a 6000 ans, une femme, la reine Shamsa, a dirigé Oman ? - Rawas, Isam al- (La femme omanaise sur le chemin de la parité, 2019)
Keywords: Vie politique – Oman – 1970-2020

Oman, un exemple positif d'application du droit de la femme - Bockel, Jean-Marie (La femme omanaise sur le chemin de la parité, 2019)
Keywords: Vie politique – Oman – 1970-2020

La femme omanaise sur le chemin de la parité - Sassine, Georges (L'Harmattan, 2019)
Keywords: Vie politique – Oman – 1970-2020

Security in the Gulf: The View from Oman - Bahgat, Gawdat (Middle East Policy, 2023)
For a long time, analysts of the Middle East have justifiably focused their attention on Qatar, Saudi Arabia, and the United Arab Emirates, three Gulf states holding massive hydrocarbon deposits and financial resources. Their leaders are the main “movers and shakers” of regional affairs and enjoy tremendous influence on the international scene. Still, other Gulf states play significant roles in shaping the Middle East's economic and strategic landscape. Such is the case with Oman, which has been a major US ally in most regional crises and has played a crucial role in mediating Gulf conflicts. This article, based on several visits to the sultanate and interviews with senior officials, analyzes the domestic, regional, and international dynamics being navigated by Sultan Haitham bin Tarik, who succeeded Sultan Qaboos bin Said in January 2020. The argument is that the new Omani leader is likely to follow the domestic and foreign policies of his predecessor, with minor adjustments. Oman may witness major changes when Crown Prince Theyazin succeeds his father. For now, given the crucial role Muscat plays in mediating regional conflicts, the sultanate expects more attention from its counterparts in Washington.
Keywords: Vie politique – Oman – 1970-2020

Contestation and Co-optation in the Desert Landscapes of Oman - Chatty, Dawn (Life Worlds of Middle Eastern Oil: Histories and Ethnographies of Black Gold, 2023)
Mobile peoples in the Middle East and elsewhere in the world have faced enormous pressure throughout the twentieth and twentieth-first centuries to change their way of life, to settle down and remain in one place. The notion that a settled existence is more modern than a mobile one continues to dominate expert thinking as a continuation of late nineteenth-century social evolutionist theories of the progress of civilisation. Most of the modern nation-states of the Middle East have approached their mobile pastoral peoples with a determined view to making them stay put in one place and give up their pastoral subsistence livelihoods. Settlement schemes, it was assumed, would assure political and economic control over these difficult-to-emplace-and-control peoples. The development aid efforts, both bi-lateral and international, throughout the twentieth century followed these same biases and were designed to make mobile or nomadic peoples ‘modern’, using principles developed during the colonial era such as terra nullius, which declared all land not held privately as empty, and thus belonging to the state so that it could be disposed of or developed as the state wished. By the end of the twentieth century, most pastoral peoples’ grazing lands had been expropriated and sed-entarisation schemes of one sort or another were the mechanisms of choice. Pastoral peoples in Oman, however, had some success in challenging the notion of terra nullius in the deserts of the country. A younger generation of ‘citizen’ herders have been able to parlay further multinational oil industry intervention to support their continued mobility in the deserts of Oman and subsistence pastoral livelihoods.I begin the chapter with a brief examination of the ways in which mobile pastoral communities in the Middle East have faced and then navigated around government land expropriation and sedentarisation efforts to create multi-resource livelihood successes without always being forced to settle. I then examine the situation in Oman, where a more ‘enlightened’ state policy regarding settlement was enacted and where oil concerns have been paramount. Determined to provide social benefits to its mobile pastoral communities without forcing them to settle, the government of Oman extended basic services to these communities late into the twentieth century.
Keywords: Vie politique – Oman – 1970-2020

The Maritime Silk Road: Implications for Oman’s Foreign Policy - Tekir, Gökhan (Ortadoğu Etütleri, 2022)
This study seeks to analyze the implications of Oman’s participation in the Maritime Silk Road, which is the maritime component of the Belt and Road Initiative, announced in 2013 by the President of the People’s Republic of China, Xi Jinping. Sultan Qaboos has transformed Oman from an isolated and backward country to an active political mediator in the region. Oman’s neutral stance and diplomatic connections with every political actor in the region differentiate Oman from the rest of the Gulf countries. Geographically, Oman is situated in the intersection of the Persian Gulf, the Arabian Sea and the Indian Ocean. Historically, Oman ruled South Asian and East African coasts, extending its influence. The geographical position and historical legacy make Oman as a key country for the Maritime Silk Road. Thus, participation of Oman in the Belt and Road Initiative is invaluable in the eyes of the Chinese policymakers. Omani policymakers, who want to diversify Oman’s economy, welcome Chinese investments. However, increasing Chinese involvement in Oman’s economy might harm Oman’s sovereignty because of Chinese practice of using debts as exerting pressure on the lending states’ sovereignty. Moreover, the intensified competition between the USA and China in the Indian Ocean could compromise Oman’s neutral stance. Yet, Sultan Qaboos’ legacy is followed by Omani policymakers. While benefiting Chinese economic investments, Oman performs balancing acts against China.
Keywords: Vie politique – Oman – 1970-2020

Deterrence through Diplomacy: Oman's Dialogue Facilitation Initiatives during the Yemeni Civil War - Ramani, Samuel (Middle East Journal, 2021)
In contrast to other states in the Gulf Cooperation Council, Oman has declined to participate in the Saudi-led military intervention in Yemen and has opted to facilitate dialogue between the conflict's warring parties. Oman has embraced a strategy of diplomatic deterrence in Yemen, facilitating dialogue to counter the perceived threats that Saudi Arabia and the United Arab Emirates pose to its foreign policy independence. The article explores how the Sultanate's diplomatic deterrence strategy manifests at the local, regional, and international levels, building on English- and Arabic-language source material and interviews.
Keywords: Vie politique – Oman – 1970-2020

Muscat and Sultan Qaboos: The Omanization of Muscat and the Muscatization of Oman - Guirado Alonso, Javier (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Vie politique – Oman – 1970-2020

Public Health and the Omani Renaissance - Foley, Sean (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Vie politique – Oman – 1970-2020

Nation and State in Oman: The Initial Impact of 1970 - Peterson, John E. (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Vie politique – Oman – 1970-2020

Constitutional Reforms During the Reign of Sultan Qaboos - Kharusi, Salim al- (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Vie politique – Oman – 1970-2020

In the Middle of a Reign - Hoffman, Valerie J. (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Vie politique – Oman – 1970-2020

From the First Renaissance to the Second: The Historical and Legal Basis for the Sultanate - Salimi, Abdulrahman al- (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Vie politique – Oman – 1970-2020

The Multiple Legacies of Sultan Qaboos: Heritage and Omani Nation Building - Penzier-Hightower, Victoria; Worrall, James (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Vie politique – Oman – 1970-2020

The Legacy of Sultan Qaboos: A Historiographical Note - Rabi, Uzi (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Vie politique – Oman – 1970-2020

Introduction: Sultan Qaboos, Omani Society, and the “Blessed Renaissance”, 1970–2020 - Fromherz, Allen (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Vie politique – Oman – 1970-2020

Oman and the Middle East Crisis (2014-2020) - Cole, Juan (2020)
Organisateur: Georgia State University
Keywords: Vie politique – Oman – 1970-2020

Friend to All, Enemy to None': Oman's Quiet Diplomacy since 1970 - Owtram, Francis (2020)
Organisateur: Georgia State University
Keywords: Vie politique – Oman – 1970-2020

Beyond the horizon and back: narrative reflection from Sultan Qaboos scholarship recipients - Pritt, Jody (2020)
Organisateur: Georgia State University
Keywords: Vie politique – Oman – 1970-2020

Development of Cultural and Literary life in Oman during the reign of Sultan Qaboos - Foley, Sean (2020)
Organisateur: Georgia State University
Keywords: Vie politique – Oman – 1970-2020

Development of Cultural and Literary life in Oman during the reign of Sultan Qaboos - Michalak-Pikulska, Barbara (2020)
Organisateur: Georgia State University
Keywords: Vie politique – Oman – 1970-2020

Muscat and Sultan Qaboos: The Omanization of Muscat and the Muscatization of Oman - Guirado Alonso, Javier (2020)
Organisateur: Georgia State University
Keywords: Vie politique – Oman – 1970-2020

The Postage Stamps of Oman during the Reign of Sultan Qaboos: Stamps as Messengers of the Renaissance - Allen, Jr, Calvin H. (2020)
Organisateur: Georgia State University
Keywords: Vie politique – Oman – 1970-2020

Greening Oman: Muslim Environmentalism, Sustainable Development, and Post Oil Futures - Curtis, Maria F. (2020)
Organisateur: Georgia State University
Keywords: Vie politique – Oman – 1970-2020

The Multiple Legacies of Sultan Qaboos: Heritage and Omani Nation Building - Penzier-Hightower, Victoria; Worrall, James (2020)
Organisateur: Georgia State University
Keywords: Vie politique – Oman – 1970-2020

Sultan Qaboos, Religious Pluralism and the Middle Path - Bos, Michael (2020)
Organisateur: Georgia State University
Keywords: Vie politique – Oman – 1970-2020

In the Middle of a Reign - Limbert, Mandana E. (2020)
Organisateur: Georgia State University
Keywords: Vie politique – Oman – 1970-2020

The Interpretation of Islam under Sultan Qaboos - Hoffman, Valerie J. (2020)
Organisateur: Georgia State University
Keywords: Vie politique – Oman – 1970-2020

From the First Renaissance to the Second: The Historical and Legal Basis for the Sultanate - Salimi, Abdulrahman al- (2020)
Organisateur: Georgia State University
Keywords: Vie politique – Oman – 1970-2020

Nation and State in Oman: The Initial Impact of 1970 - Peterson, John E. (2020)
Organisateur: Georgia State University
Keywords: Vie politique – Oman – 1970-2020

Speaking of the Renaissance: Sultan Qaboos and his Speeches - Fromherz, Allen James (2020)
Organisateur: Georgia State University
Keywords: Vie politique – Oman – 1970-2020

An Examination of Political and Social Conditions of Ibadism in Contemporary Oman (The Reign of King Qaboos) - Mehr, Seyed Jalal Razavi; Mohammadi, Ramezan; Shojaiyan, Mohammad; Farrahi, Abdollah (Islamic Denominations, 2024)
Keywords: Vie politique – Oman – 1970-2020

Sultan Qaboos and the Modernization of Oman - Kirichenko, V. (Russia and the Moslem World, 2021)
Keywords: Vie politique – Oman – 1970-2020

A Sultanate that Endures: Oman in the World from Qaboos bin Sa'id to Haitham bin Tariq - Kechichian, Joseph Albert (Liverpool University Press, 2023)
Qaboos bin Sa'id, Sultan of Oman from 1970 until his death in 2020, marked Omani history. He belonged to that very small circle of leaders who solemnized their time in power, transforming the Sultanate by empowering generations of citizens to lead constructive and fulfilling lives. Joseph Kéchichian provides a full assessment of the fourteenth Al Sa'id dynasty sovereign, setting out his vision for what was then a relatively isolated nation, championing the necessity for alliances, investing in people as well as the land, and founding key institutions that evolved over five decades. These achievements took time to materialize as Qaboo's preserved Al Sa'id rule, governed wisely, avoided internal and external political entanglements, and passed the torch to his successor Haitham bin Tariq, who validated Al Sa'id authority upon becoming Sultan. A Sultanate that Endures is a companion volume to Oman and the World: The Emergence of an Independent Foreign Policy (RAND, 1995). Ithighlights Omani history, with a particular focus on the religious creed Ibadhiyyah that embraces tolerance and prevents injustice. The transition from a theocracy to a monarchy that established dynastic rule is discussed in the context of the Sultanate's millennial history, affirming its rulers' legitimacy and citizen acceptance. The author evaluates how Ibadhiyyah and its traditions formed the gist of the Sultanate's foreign policies, concentrating on ties with predominantly Muslim-inhabited countries, engagement with the African Continent, its links with the Arab Gulf region, and appraising Omani diplomacy with key Asian and Western countries. The study closes with a preliminary analysis of the transition to Sultan Haitham, evaluates his primary appointments, and reviews his declared priorities for the nation. Future domestic and foreign policy challenges that may confront Omanis concludes the volume.
Keywords: Vie politique – Oman – 1970-2020

Oman : confiance et stabilité, les obsessions du sultan - Hoffner, Anne-Bénédicte (La Croix, 2021)
Un an exactement après son accession au trône, le sultan d’Oman a modifié les règles de transmission du pouvoir et nommé son fils aîné prince héritier. Une manière de renforcer la confiance et la stabilité, piliers essentiels du régime pour redynamiser l’économie.
Keywords: Vie politique – Oman – 1970-2020

Oman. Incertitudes économiques, défis sociaux - Müller, Quentin (Orient XXI, 2020)
Le sultanat d’Oman a été relativement épargné par le Covid-19, mais subit les conséquences d’un choc pétrolier inédit. La chute du prix des hydrocarbures pourrait (...)
Keywords: Vie politique – Oman – 1970-2020

Oman: Constitutionalism Unrealized - Said, Basma Mubarak (Al-Abhath, 2022)
This chapter analyzes the development of constitutionalism in Oman over three historic phases. It examines the establishment of the modern Omani state, and sheds light on the power struggle between the absolutist ruler, Sultan Saʿid bin Taimur al-Saʿid, and his reformist brother, Tariq bin Taimur al-Saʿid, the first serious attempt to introduce constitutionalism in Oman calling for limiting the Sultan’s power and transforming Oman into a constitutional monarchy. It details first how British authorities intervened as intermediaries in this power struggle, bolstering the Sultan’s powers and entrenching absolutist monarchy in Oman. The chapter then examines the events surrounding the late Sultan Qaboos’s issuance of the Basic Law – enacted during his twenty-sixth year in power – and situates it as a response to internal and external pressures within Oman and in the Gulf region in the mid-1990s. The chapter moves then to describe a movement for greater power-sharing emerging as part of Arab Spring-inspired protests in 2011 and describes some of the minor constitutional amendments enacted by Sultan Qaboos that year, which did little to alter the status quo. Finally, it examines the Sultan’s passing away in January 2020, the appointment of Sultan Haitham as successor, and his enactment of a new constitutional document intended to stabilize governance in Oman and devolve some authority to his inner circle, while largely avoiding a larger disruption of power dynamics.
Keywords: Vie politique – Oman – 1970-2020

Sultan Qaboos and modern Oman, 1970-2020 - Fromherz, Allen James; Salimi, Abdulrahman al- (Edinburgh University Press, 2022)
This is the first, timely account of the modern Oman over the entire reign of Sultan Qaboos (1970-2020). The book provides unique, wide-ranging interdisciplinary and international perspectives on modern Oman by specialists in a variety of fields from Oman, Europe and North America. Utilising a range of perspectives, all chapters connect to the theme of rebirth, of the connections between the past and the future pursued by Sultan Qaboos and his government in fields as diverse as health, religion, law, economy, heritage and diplomacy. Not overlooking the many challenges faced during Sultan Qaboos' reign and still faced by Oman, the book engages various theories and perspectives about Oman's economic, religious, educational and cultural transformations under Qaboos (d. 2020 CE)
Keywords: Vie politique – Oman – 1970-2020

Baloch Mashkat (Muscat) and the Sultan Qaboos Era: Cultural Performance, Cosmopolitanism, and Translocal Consciousness - Murer, George (Arabian Humanities, 2022)
Baloch cultural life in Muscat is a vivid part of Oman's national landscape as it has evolved from the time the late Sultan Qaboos took power. Although often typecast as soldiers or police officers, Omani Baloch are deeply integrated into a broad spectrum of professions and social milieus. These include communities of arts and letters at the heart of the Omani cultural renaissance championed by the late Sultan and embodied in institutions such as Royal Opera House, the Muscat International Film Festival, and the Oud Hobbyists Association. The many nuances to Baloch identity have led to a plurality of social spaces, from literary forums intertwined with South Asian intellectual spheres to ceremonial contexts in which Omanis of Baloch, Peninsular Arab, and East African heritage converge. Networks of patronage and transnational circulations of songs and poetry among Baloch attest to the longevity of Western Indian Ocean circuits of cultural exchange.
Number: 15
Keywords: Vie politique – Oman – 1970-2020

A Political Culture and Foreign Policy Shaped by a Moderate Religious View: The Case of the Sultanate of Oman - Rabi, Uzi (2009)
Keywords: Vie politique – Oman – 1970-2020

Ibadism and Omani Nation-Building since 1970 - Valeri, Marc (2009)
Keywords: Vie politique – Oman – 1970-2020

The Omani Equation: A Road Map for a Better Middle East - Rabi, Uzi (2019)
Keywords: Vie politique – Oman – 1970-2020

A political culture and foreign policy shaped by a moderate religious view - the case of the Sultanate of Oman - Rabi, Uzi (2011)
Keywords: Vie politique – Oman – 1970-2020

Political Development and its Role in the Stability of the Sultanate of Oman (1981 - 2012) = التنمية السياسية ودورها في الاستقرار السياسي في سلطنة عمان (1981-2012) - الدرمكي, علي بن سليمان بن سعيد (جامعة الشرق الأسط, 2012)
Keywords: Vie politique – Oman – 1970-2020

Immunizing Against Sectarian “Sickness”: The Case of Oman - Goldsmith, Leon (Middle East Institute, 2015)
The political culture in Oman seems to foster a pluralist intermeshing of national and sub-national identities that other diverse Arab states like Syria and Iraq were at pains to eliminate. This essay examines the Omani case to explore whether there are any lessons to be learned about sectarianism and how it can be confronted in the wider Middle East.
Keywords: Vie politique – Oman – 1970-2020

The Year of Oman's Discontent - Peterson, John E. (The Middle East in London, 2011)
Keywords: Vie politique – Oman – 1970-2020

Oman's Sultan 'in good health' amid successor speculations (Middle East Eye, 2015)
Speculation grows over who could succeed Sultan Qaboos as he continues treatment in Germany over Eid holiday
Keywords: Vie politique – Oman – 1970-2020

Le Sultanat d’Oman : une exception régionale - Rouxel, Mathilde (Les clés du Moyen-Orient, 2016)
Keywords: Vie politique – Oman – 1970-2020

The Next Middle East Crisis Will Start If This Man Dies - Rubin, Michael (Business Insider, 2014)
The 74-year-old sultan has left no clear successor.
Keywords: Vie politique – Oman – 1970-2020

“Oman after Qaboos will be more dependent on the UK and the US” - Valeri, Marc (My East-West, 2015)
Marc Valeri is Senior Lecturer in Political Economy of the Middle East, Director of the Centre for Gulf Studies at the University of Exeter, in the United Kingdom. An expert on the Sultanate that w…
Keywords: Vie politique – Oman – 1970-2020

“Qaboos can make mistakes like anybody else"– The Sultan of Oman De-sacralized - Valeri, Marc (Jadaliyya - جدلية, 2012)
The summer of 2012 in Oman was punctuated by a litany of reports announcing arrests and convictions of bloggers and human rights activists. This new crackdown on civil society started in May, when two human rights activists and a lawyer were arrested whil
Keywords: Vie politique – Oman – 1970-2020

Autoritarisme et stratégies de légitimation dans le golfe Persique à l'heure du « Printemps arabe » - Valeri, Marc (Revue internationale de politique comparée, 2012)
Keywords: Vie politique – Oman – 1970-2020

High Visibility, Low Profile: The Shiʿa in Oman Under Sultan Qaboos - Valeri, Marc (International Journal of Middle East Studies, 2010)
If the U.S. invasion of Iraq in 2003 has produced unprecedented consequences for the internal policies of Middle Eastern regimes, this is not related to the upsurge of democratization that was supposed to spread like a contagion through the neighboring countries. Rather, it is due to the increased impact of the Shiʿi issue on the national political agendas of many Arab states. Following the collapse of Saddam Hussein's regime, many observers thus drew attention to the emergence of what they regarded as a Shiʿi “revival” in the Middle East—a perception that the military success of the Lebanese Hizbullah against Israel in the summer of 2006 seemed to confirm.
Keywords: Vie politique – Oman – 1970-2020

Le Conseil d'Oman, une instance bicamérale de consolidation de l'autoritarisme sultanien - Valeri, Marc (Revue internationale de politique comparée, 2008)
Depuis 1996, le sultanat d’Oman dispose d’un parlement bicaméral, le Conseil d’Oman, composé d’une chambre haute, le Conseil d’état, nommée intégralement par le sultan, et d’une chambre basse, le Conseil Consultatif, élue au suffrage universel tous les quatre ans. Ce texte s’interroge sur le rôle de cette institution, dans un pays gouverné depuis 1970 par un souverain (Qabous Al Said) qui a su concilier un développement économique et social sans précédent avec la personnalisation du pouvoir la plus élaborée de toute la Péninsule arabique.
Keywords: Vie politique – Oman – 1970-2020

Au sultanat d'Oman, de nouveaux défis pour une fin de règne - Lavergne, Marc (Diplomatie : affaires stratégiques et relations internationales, 2017)
Mascate jouit depuis des décennies d'une réputation enviable, celle d'un pays discret et stable, bénéficiant d'une relative aisance, sous la férule bienveillante d'un despote éclairé. Mais à l'image de son souverain affaibli par l'âge et la maladie, et îlot de paix voit son équilibre mis à l'épreuve par l'émergence de difficultés économiques et par les conflits régionaux.
Keywords: Vie politique – Oman – 1970-2020

Oman est-il vraiment la seule anomalie paisible du Moyen-Orient ? - Miller, Madeleine (Middle East Eye, 2016)
Encensé comme l’incarnation de la stabilité, le sultan Qabus poursuit la réussite remarquable d’Oman… mais à quel prix ?
Keywords: Vie politique – Oman – 1970-2020

Oman: Will the Imamate Return? - Katz, Mark N. (Travels and Observations, 2014)
Some twenty years ago, I wrote up the following notes for myself after reading John C. Wilkinson’s The Imamate Tradition of Oman (Cambridge University Press, 1987): While Omanis are virtually all M…
Keywords: Vie politique – Oman – 1970-2020

Assessing the Political Stability of Oman - Katz, Mark N. (2004)
Oman is facing important economic and political challenges. The economic challenge it faces is that its population is rising while its oil reserves are declining. The political challenges it faces are the extreme concentration of authority in the hands of one man (Sultan Qaboos), the sultan's unwillingness to allow meaningful political participation or dialogue, political legitimacy issues concerning both Sultan Qaboos and the succession process he has set up, and sporadic but persistent signs of opposition. This article examines these problems and assesses their implications for the political stability of Oman.
Keywords: Vie politique – Oman – 1970-2020

Histoire : à Oman, le roi se meurt - Saint-Périer, Laurent de (Jeune Afrique (site web), 2014)
La maladie dont souffre l’atypique sultan Qabous pose la question de la succession, qui s’annonce d’autant plus délicate que le souverain s’est façonné un État sur mesure et n’a pas d’héritier. – Jeune Afrique
Keywords: Vie politique – Oman – 1970-2020

Remembering His Majesty Sultan Qaboos - Schmierer, Richard J. (Middle East Policy, 2020)
Keywords: Vie politique – Oman – 1970-2020

Oman pardons 31 coup plotters (BBC News, 2005)
Thirty-one Omanis convicted of trying to overthrow the government are pardoned by the state's ruler.
Keywords: Vie politique – Oman – 1970-2020

Oman jails 31 for plotting coup (BBC News, 2005)
A total of 31 suspected Islamists in Oman get sentences of up to 20 years in jail for plotting a coup.
Keywords: Vie politique – Oman – 1970-2020

Oman 'arrests hundreds over plot' (2005)
At least 100 people are reportedly arrested in Oman amid rumours of a planned attack on a festival.
Keywords: Vie politique – Oman – 1970-2020

Le tournant vert qui déboussole Oman - Castelier, Sebastian (Orient XXI, 2021)
Un an après le décès du sultan Qabous Ben Saïd Al-Saïd, le « père de la nation », Oman tâtonne dans un monde où la suprématie du pétrole s’essouffle, au profit des (...)
Keywords: Vie politique – Oman – 1970-2020

Le sultan d'Oman restructure le pouvoir - Delozier, Elana (Orient XXI, 2020)
Dans une série de décrets royaux qui dénotent un fort recentrage sur l’économie, le sultan Haïtham Ben Tarek Ben Taïmour Al-Saïd a, pour la première fois, délégué (...)
Keywords: Vie politique – Oman – 1970-2020

Oman. Le nouveau sultan face à cinq défis - Arafat, Alaeddine (Orient XXI, 2020)
Conformément au testament du sultan Qabous Ben Saïd (1940-2020) ouvert après son décès, et contrairement aux prévisions de nombreux Occidentaux, le pouvoir est (...)
Keywords: Vie politique – Oman – 1970-2020

Succession incertaine à Oman - Qui remplacera le sultan Qabous ? - Valeri, Marc (Orient XXI, 2014)
Oman a servi d’intermédiaire entre les États-Unis et l’Iran et joue un rôle diplomatique actif dans la région. D’où l’inquiétude — partagée par la population — que (...)
Keywords: Vie politique – Oman – 1970-2020

After Qaboos, who will be Oman's next sultan? - Riedel, Bruce (Al-Monitor, 2015)
Now that Saudi Arabia has seen its succession through, attention has moved to who will succeed Oman's Sultan Qaboos, who has been in Munich since the summer for unspecified health reasons.
Keywords: Vie politique – Oman – 1970-2020

Entretien avec Marc Valeri – Le point sur Oman - Chaigne-Oudin, Anne-Lucie; Valeri, Marc (Les clés du Moyen-Orient, 2016)
Keywords: Vie politique – Oman – 1970-2020

The Sultanate of Oman: Sons and Daughters - Arslanian, Artin H. (Digest of Middle East Studies, 2013)
Keywords: Vie politique – Oman – 1970-2020

The Sultanate of Oman: Resistant to Violent Extremism? - Caputo, Alexandra (Charles University, 2018)
This thesis analyses the Sultanate resistance to violent extremism as a Middle Eastern nation that has consistently scored a “0” on the Global Terrorism Index (GTI), an ongoing indexing of global terrorism from 2003 onwards. The Sultanate was markedly stable for those years unaccounted by the GTI. This case study examines institutional and legal frameworks established by the Sultanate and their value on countering radicalization and extremism processes that might lead to an act of terrorism. This research is supported by literature on radicalization and countering violent extremism (CVE) models, with great focus on a five-pronged, comprehensive working paper that approaches major problems across the Middle East. Radicalization and extremism notably fester in such problematic approaches, and the objective is to parallel these problems with the strategies, approaches, and norms of the Sultanate of Oman to see if this paper can come to a conclusion about the ability of nations and their populations to resist radical pathways and extremist ideologies. With religion at the crux of manipulation and blame-games, the religious doctrine of Oman also becomes a vital component of this study. Ibadism, a sect of Islam, is widely practiced in Oman and its’ tenants are deeply rooted in social and legal qualities.
Keywords: Vie politique – Oman – 1970-2020

Oman : entre continuité et incertitude - Mekkaoui, Abderrahmane (Centre Français de Recherche sur le Renseignement, 2018)
Politologue, spécialiste des questions sécuritaires et militaires (Maroc). Membre du Collège des conseillers internationaux du Centre Français de Recherche sur le Renseignement (CF2R). Le processus de succession du sultan Qabous Ibn Taymour Ben Saïd (77 ans) vient enfin d’être lancé en grande pompe, directement après l’annonce de la nomination d’Asåad ben Tarek ben Taymour Al-Saîd, cousin […]
Keywords: Vie politique – Oman – 1970-2020

Oman: défis intérieurs et enjeux régionaux dans la perspective de l’après-sultan - Dazi-Héni, Fatiha (IRSEM, 2017)
Cette note expose les principaux enjeux intérieurs et extérieurs dans le contexte d’une succession possible du sultan Qabous, dont l’état de santé s’est aggravé en 2014. Son remplacement sera difficile à assurer en raison du statut de père de la Nation dont jouit le sultan, qui a sorti son pays de l’ère féodale. Il l’a modernisé et l’a doté d’une diplomatie de médiation devenue incontournable dans une région propice aux tensions et conflits. À court terme, la tâche du successeur s’avèrera la plus ardue, en raison de la baisse des prix du pétrole qui affecte la situation économique. À moyen terme, l’enjeu sera de renouveler un pacte social à bout de souffle. Cependant, le rôle de médiation de la diplomatie omanaise dans la région et de facilitateur entre Washington et Téhéran, ajouté à sa position stratégique, au carrefour de la Route de la soie, plaident pour qu’acteurs régionaux et globaux soutiennent le sultanat de l’après-Qabous.
Keywords: Vie politique – Oman – 1970-2020

Can Oman’s Stability Outlive Sultan Qaboos? - Cafiero, Giorgio; Karasik, Theodore (Middle East Institute, 2016)
Keywords: Vie politique – Oman – 1970-2020

Sultanate of Oman: A happy symbiosis - Thurner, Ingrid (Qantara.de - Dialogue with the Islamic World, 2018)
It is rare that a ruler is able to concentrate so much power in his own hands while remaining popular with his subjects: Sultan Qaboos has achieved a synthesis of tradition and globalisation. By Ingrid Thurner
Keywords: Vie politique – Oman – 1970-2020

Louvain : pour accueillir le sultan d’Oman et sa suite, l’hôtel The Fourth met dehors ses autres hôtes - Mil, Richard (Résistance Républicaine, 2019)
. The Fourth Leuven La santé du sultan d’Oman apprécie beaucoup celle des Flandres… . L’hôtel The Fourth à Louvain – flamboyante cité flamande à 25 km à l’est de Bruxelles –…
Keywords: Vie politique – Oman – 1970-2020

Qui est ce sultan qui a réservé un hôtel entier pour deux mois à Leuven ? (vivreici, 2019)
Keywords: Vie politique – Oman – 1970-2020

The emergence of post-traditional Oman - Peterson, John E. (University of Durham, 2005)
Keywords: Vie politique – Oman – 1970-2020

America and Oman: The Context for Two Nearly Centuries of Relations - Peterson, John E. (2014)
Keywords: Vie politique – Oman – 1970-2020

Quel avenir pour le Sultanat d'Oman ? - Vagile, Juliette (Aujourd'hui la Turquie, 2014)
Les rumeurs de cancer et la raréfaction des apparitions du Sultan d’Oman inquiètent les citoyens de son pays : Qabous ben Saïd, n’ayant pas d’enfant, n’a effectivement pas de descendance directe, …
Keywords: Vie politique – Oman – 1970-2020

Oman: A State Elaborating a Nation - Peterson, John E. (Italian Institute for International Political Studies, 2019)
Keywords: Vie politique – Oman – 1970-2020

Simmering Unrest and Succession Challenges in Oman - Valeri, Marc (Carnegie Endowment for International Peace, 2015)
Keywords: Vie politique – Oman – 1970-2020

Oman’s mediatory efforts in regional crises - Valeri, Marc (Norwegian Peacebuilding Resource Centre, 2014)
Oman’s role in facilitating the conclusion of the Iran-P5+1 nuclear deal in November 2013 and its announcement a few weeks later that it would not join a proposed Gulf union can be understood within a recent history of conciliatory efforts intended to promote negotiated solutions to regional crises. Oman has always perceived political instability in the Gulf and West Asia as a factor threatening the country’s own internal stability. This perception of political vulnerability also explains the sultanate’s determination to prevent foreign actors from interfering in its internal affairs. The price for this independent foreign policy towards its neighbours has been the country’s unquestioned political and military dependence on Britain and the U.S. Given Oman’s strategic importance to the security of the entire Gulf, controlling as it does the Strait of Hormuz, through which approximately one-third of the world’s seaborne trade in crude petroleum passed in 2013, Britain and the U.S. have shared Muscat’s aversion for any disruption of its internal status quo and wish to prevent any contamination of Omani territory by unwanted foreign influence.
Keywords: Vie politique – Oman – 1970-2020

Democracy in Slow Motion: Oman Goes to the Polls - Carpenter, J Scott; Henderson, Simon (The Washington Institute for Near East Policy, 2017)
Keywords: Vie politique – Oman – 1970-2020

Oman faces the Twenty-First Century - Peterson, John E. (Political change in the Arab Gulf States: stuck in transition, 2011)
Keywords: Vie politique – Oman – 1970-2020

Britain and the Gulf: At the Periphery of Empire - Peterson, John E. (The Persian Gulf in history, 2009)
Keywords: Vie politique – Oman – 1970-2020

Life after Oil: Economic Alternatives for the Arab Gulf States - Peterson, John E. (Mediterranean Quarterly, 2009)
Keywords: Vie politique – Oman – 1970-2020

The Solitary Sultan and the Construction of the New Oman - Peterson, John E. (Governance in the Middle East and North Africa: a handbook, 2013)
Keywords: Vie politique – Oman – 1970-2020

Oman: the present in the context of a fractured past - Barrett, Roby Carol (Joint Special Operations University, 2011)
"Dr. Roby Barrett's examination and study of some 200 years of the Sultanate of Oman's dynastic history is an excellent companion piece to his earlier work, Yemen: A Different Political Paradigm in Context. His Oman study puts into context the last four decades of the Sultanate's history to answer the question of whether Oman has changed fundamentally from a nation fraught with instability and conflict to one of peace and stability. Dr. Barrett's research focuses on the current rule of Sultan Qaboos and his approach to change, development, and modernity in a centuries-old culture that has experienced political, economic, and social upheaval throughout most of its early existence."–Page ix.
Keywords: Vie politique – Oman – 1970-2020

9th June - Den glemte krig i Oman / The forgotten war in Oman - Allarp, Poul Mikael (2015)
Keywords: Vie politique – Oman – 1970-2020

Oman succession unlikely to jeopardise stability (Oxford Analytica, 2012)
Sultan Qaboos bin Said Al Bu-Said lacks a direct heir and refuses to groom a successor. As he...
Keywords: Vie politique – Oman – 1970-2020

Chasse aux cyberactivistes à Oman (Reporters sans frontières, 2015)
Les nombreuses arrestations et condamnations d’utilisateurs de réseaux sociaux et blogueurs traduisent l’état de la liberté d’information et d’expression sur la Toile au sultanat d’Oman. Sous des accusations d’insultes à l’émir ou d’incitation à des rassemblements illégaux et troubles à l’ordre public, les cybermilitants qui font un travail d’information sont interpellés, parfois détenus au secret et condamnés à de lourdes peines. “La situation de la liberté d’information et d’expression à Oman est déplorable et les autorités s’acharnent contre les cyberactivistes pour leur travail en faveur des droits de l’homme et des libertés fondamentales. Détenir des militants dans des lieux secrets pour les interroger des jours durant et les faire disparaître ainsi aux yeux de leurs proches est scandaleux. RSF appelle à leur libération immédiate et inconditionnelle”, déclare Lucie Morillon, directrice des programmes de l’organisation. Saeed Jaddad, militant des droits de l’homme, très actif lors des soulèvements de 2011, a été condamné le 31 mars 2015 à un an de prison et une amende de 1000 rials (environ 2400 euros) en vertu de la loi sur la cybercriminalité par le tribunal de première instance de la ville de Salalah dans la province de Dhofar. Son avocat a affirmé que le blogueur avait été condamné pour un article, publié en octobre 2014, dans lequel il faisait un parallèle entre les révoltes de 2011 à Dhofar et celles de 2014 à Hong Kong. Il est officiellement interdit de publication dans les médias omanais. Il avait déjà été condamné le 8 mars dernier à trois ans de prison et une amende de 1700 rials (environ 4800 euros) par le tribunal de première instance à Mascate pour ‘atteinte au prestige de l’Etat’, ‘incitation à manifester’ et pour l’’utilisation de réseaux sociaux pour publier des informations pouvant causer des troubles à l’ordre public’. Saeed Jaddad est détenu par les autorités depuis son arrestation à son domicile à Salalah le 21 janvier 2015. Ce militant est dans le collimateur des autorités depuis quelques années et a été maintes fois arrêté et relâché sous caution. Récemment, en octobre 2014, il avait été stoppé à l’aéroport et empêché de se rendre à un évènement organisé par Front Line Defenders à Istanbul à cause d’une interdiction de voyager, qu’il ignorait, émise depuis le mois de juillet 2014. Il avait ensuite été arrêté et interrogé dans un lieu secret pendant 12 jours en décembre 2014. Taleb Saedi est un activiste de la Toile qui a disparu après avoir été interpellé par les autorités le 23 mars 2015 pour interrogation. Il est connu pour ses écrits critiques, ses appels aux réformes politiques et sociales sur les réseaux sociaux et son travail sur les activistes détenus par les forces de sécurité. Il avait déjà été interpellé en juillet 2014 pour avoir appelé à la manifestation pacifique en solidarité avec le peuple palestinien. Le célèbre blogueur Muawiya Al-Rawahi, arrêté de nombreuses fois depuis 2011 et dont la dernière arrestation date du mois de février dernier pendant une semaine, a été interpellé par les autorités émiraties le 24 février 2015 alors qu’il cherchait à se rendre en voiture aux Emirats. Depuis on est sans nouvelles de lui. Le blogueur est connu pour son utilisation des réseaux sociaux en plus de son blog et pour ses propos critiques du régime en faveur de réformes. Ces trois cas ne sont pas isolés puisque de nombreux militants sont arrêtés pour avoir exercé leur droit à la liberté d’expression et d’information. Oman figure à la 127e place sur 180 du Classement 2015 de la liberté de la presse établi par Reporters sans frontières.
Keywords: Vie politique – Oman – 1970-2020

Oman: Quo vadis Märchensultanat? - Richter, Thomas (Giga, 2014)
Keywords: Vie politique – Oman – 1970-2020

Nobody Knows Who'll Be in Charge after Oman's 'Founding Father' - Lees, Kevin A. (The National Interest, 2016)
The sultan has no brothers, no wife, no sons and no clear successor.
Keywords: Vie politique – Oman – 1970-2020

Oman, the Land of No Jihad - McCants, Will (2008)
Ekhlaas member al-Suhayl observes that JIhadis criticize Saudi Arabia, Kuwait, Qatar and other Arab countries for collaborating with the United States, but they say nothing about Oman. Moreover, Oman
Keywords: Vie politique – Oman – 1970-2020

Kudos and follow-up questions for reporting on imam Ghalib's death - Pitterle, Elissa G. (Secretary State, 2006)
Keywords: Vie politique – Oman – 1970-2020

Place and Role of Shura Council in Oman Law System - Busaidi, Y. Y. al- (2013)
The article examines radical changes both in the procedure of Shura Council formation and in its field of competence. The structure of the Council comes under review and the place and role of its main authorities in supporting the government on different running the state issues is determined. Considering and examining the many years' experience of the Council the author has come to the conclusion that the role of the Shura Council is limited only by the government in addressing certain issues. The Council studies these issues and provides recommendations to the Sultan for approval. These recommendations have no legal force, and the Council cannot impose its views on the Government. Despite this fact, the Council in its current form can become the basis for the future Parliament of Oman. To make this happen, in our opinion, it is necessary that the Council be directly involved in the discussion and approval of the state budget. It is also important to make the government accountable to the Council and to report to him about the results of its work.
Keywords: Vie politique – Oman – 1970-2020

Peculiarities of Oman Imamate Law System - Busaidi, Y. Y. al- (2013)
The article examines the evolution and peculiarities of the Imamate institute in Oman. Special attention is paid to the Ibadi movement of Islamic law as well as to the tribal common law both of which form the basis for the analysis of the role of Shura Council and influential circles for the purpose of gaining certain balance in relations between the authorities of the country and its inhabitants. Our analysis shows that until the middle of the XX century Oman was a union of tribes supporting Ibadi Islam. Within Ibadi doctrine for the first time in the history of Muslim societies the principles of people's participation in public administration were developed, which resulted in the outward expression in imamate moderate state system. Imam ruled the country with the help of the Council of theologians, the Shura Council, as well as governors and heads of tribes. For centuries Imamate and its institutions ensured the safety of society and order in social relations. Oman Imamate guaranteed gradual strengthening of the tradition of social relations and its steadiness. The effectiveness of such a form was confirmed by the fact that such statehood existed for twelve centuries.
Keywords: Vie politique – Oman – 1970-2020

The Implications of Legal Change and Political Reform for the Workings of the Majlis A' Shura and Majlis A' Dawlah in Oman (1981-2003) - Kathiri, Said Masoud Naoom al- (Durham University, 2007)
Keywords: Vie politique – Oman – 1970-2020

Domesticating Local Elites. Sheikhs, Walis and State-Building Under Sultan Qaboos - Valeri, Marc (Regionalizing Oman: Political, Economic and Social Dynamics, 2013)
Keywords: Vie politique – Oman – 1970-2020

Oman : un ilôt de stabilité, loin des passions sunnite et chiite - Ghorbal, Sami (Jeune Afrique (site web), 2015)
Keywords: Vie politique – Oman – 1970-2020

The Limits of the Sandhurst Connection: The Evolution of Oman’s Foreign and Defense Policy, 1970–1977 - Gardner, Nikolas (The Journal of the Middle East and Africa, 2015)
This article examines the role of Sultan Qaboos bin Said Al Said in the development of Oman’s foreign and defense policy from 1970 to 1977. Historians have assumed that following the British-orchestrated overthrow of Qaboos’s father in 1970, British soldiers and diplomats exerted a decisive inﬂuence over the inexperienced young sultan’s policy decisions. While Qaboos certainly depended on British military assistance to defeat an insurgency in Oman’s Dhofar province, he proved much more assertive than existing accounts have suggested. Drawing on British archival documents as well as correspondence of American advisors to the sultan, this article shows that Qaboos played an active role in the development of Omani foreign and defense policy. From the beginning of his reign, the sultan enlisted a diverse group of independent advisors in order to limit British inﬂuence over his government. His assertiveness intensiﬁed as Oman enjoyed a windfall of oil wealth beginning in 1973. In demonstrating the sultan’s attempts to consolidate power from the outset of his reign, this article offers a case study of the limits of Western inﬂuence over leaders in the Gulf region.
Keywords: Vie politique – Oman – 1970-2020

A Vision of Oman: State of the Sultanate Speeches by Qaboos Bin Said, 1970–2006 - Kechichian, Joseph Albert (Middle East Policy, 2008)
Keywords: Vie politique – Oman – 1970-2020

Oman : The “Forgotten” Corner of the Arab Spring - Worrall, James (Middle East Policy, 2012)
Keywords: Vie politique – Oman – 1970-2020

Oman : between independence and colonial control 1970-1976 - Worrall, James (University of Leeds, 2008)
The British government's announcement of its intention to withdraw 'East of Suez' by the end of 1971 was the catalyst for renewed efforts to resolve many disputes in the Gulf region. Accordingly, the threat posed by the growing Marxist inspired rebellion in Dhofar to Britain's remaining interests in the area could not be left unchallenged. But the means by which this challenge was to be met (including the extent of both overt and covert support for the Sultan) in the post-Suez era, posed a number of challenges for decision-makers in Whitehall. It soon became apparent that with aid flowing to the rebels from South Arabia, the situation was rapidly deteriorating. The failure of the counter-insurgency campaign thus far was increasingly seen to be the fault of Sultan Sa'id bin Taimur whose stubborn refusal to engage in anything but repression in Dhofar and whose denial of modernity to his people in spite of increasing oil revenues meant that Sa'id came to be seen as part of the problem and not the solution. This thesis examines how officials in London defined British interests in Oman and the debates in Whitehall, under successive governments, about how best to tackle the growing insurgency. This complex balancing act between protecting British interests and influence, creating an effective indigenous administration and security bodies while maintaining the image of strategic retreat and the sovereign independence of Oman forms the focus of this thesis. Through an exploration of British government decision making regarding Oman this thesis provides a systematic re-examination of the Anglo-Omani relationship during the critical years of transformation from isolated, undeveloped state into a modern outward looking nation. Since there have been no impartial, in-depth studies of this period which have had access to a wide range of primary source documents, the thesis is able to fill a gap in the literature by demonstrating how British interests were decided upon, how foreign policy was made and how it was implemented. Through the examination of this process this thesis aims to develop a better understanding of how and why Britain decided to commit herself to the protection of the Omani regime, while, at the same time, withdrawing from the Gulf and seeking membership of the European Economic Community. Using historical methodology and drawing extensively upon newly released archival records and interviews with former officials and high ranking officers, the thesis challenges established narratives regarding Britain's role in Oman. By examining the three key pillars of British support for the Sultanate of Oman - the political, military and diplomatic - this thesis argues that the evolution of a careful, considered and sometimes parsimonious policy marked British policy towards Oman, a policy far removed from the deterministic, callous and rapacious account presented by writers such as Halliday, Newsinger and Owtram.
Keywords: Vie politique – Oman – 1970-2020

The political change in Oman from 1970 : transition towards democracy - Harthy, Abdullah Salim Hamed al- (University of Hull, 2004)
The aim of this thesis is to study the political changes in Oman from 1970 with the focus on the transition towards democracy. The core issue is the change from the policy of the previous sultan, who banned the participation of the nation and oppressed it. This led the country to civil war, isolation and the end of the regime. The current sultan, who launched a coup against his father in 1970, adopted various changes in areas such as the economy, politics and infrastructure, and allowed the people to run the country. The important changes were the process of democratisation in Oman, which is discussed in the context both of democratic theory, and change in the South. The thesis will offer an overview of democratic political theory, an account of political change in the South in general, and in the Middle East region in particular. The focus on Oman will seek to answer three questions: when did the process of democratisation begin; why was it begun, and how has it been managed? The core of the argument will look at the creation of formal institutions of democracy, such as the Majlis Ash-Shura (Consultative Council), and the State Council, and informal institutions, such as the media, the Chamber of Commerce, the Businessmen's Council, Sablat Alarab (the Arab Council Web Site), and the role of leading individuals in the democratic debate. These changes led the current sultan to receive internal and extemallegitimacy. Omani citizens are now aware of the development in other parts of the world and they will force the current sultan to add further changes. He should respond positively in order to remain in power.
Keywords: Vie politique – Oman – 1970-2020

Oman : la révolte dynastique - Allmeling, Anne (Outre-Terre, 2011)
Keywords: Vie politique – Oman – 1970-2020

Oman: politics and society in the Qaboos state - Valeri, Marc (Hurst, 2009)
Keywords: Vie politique – Oman – 1970-2020

Oman - Valeri, Marc (Encyclopedia of Islam and the Muslim World, 2016)
Keywords: Vie politique – Oman – 1970-2020

Visions of Omani Reform - Fromson, James; Simon, Steven (Survival, 2019)
Oman’s need to reduce its oil dependence illuminates the difficulty of reforming Gulf rentier states writ large.
Keywords: Vie politique – Oman – 1970-2020

The Sultanate of Oman and the Iran Nuclear Deal - Schmierer, Richard J. (Middle East Policy, 2015)
Keywords: Vie politique – Oman – 1970-2020

Muscat as a Port City - Peterson, John E. (The Gulf in Modern Times: Peoples, Ports and History, 2014)
Keywords: Vie politique – Oman – 1970-2020

Historical Muscat: an illustrated guide and gazetteer - Peterson, John E. (Brill, 2007)
Keywords: Vie politique – Oman – 1970-2020

The Baluch presence in the Persian Gulf - Peterson, John E. (Sectarian Politics in the Persian Gulf, 2013)
Keywords: Vie politique – Oman – 1970-2020

Oman: the 1966 assassination attempt on Sultan Saʿid b. Taymur - Peterson, John E. (Arabian Peninsula background note, 2004)
With a list of Omani tribes with there affiliation (Ibāḍī/Sunnī, Ghāfirī/Hināwī) and the regions where they are concentrated. The discussion in this note is taken largely from Peterson 1978, 112-114. The treatment there relies heavily on Wilkinson 1972a.
Keywords: Vie politique – Oman – 1970-2020

Oman: three and a half decades of change and development - Peterson, John E. (Middle East Policy, 2004)
Keywords: Vie politique – Oman – 1970-2020

Oman: al-Ghafiriyah and al-Hinawiyah tribal confederations - Peterson, John E. (Arabian Peninsula background note, 2003)
With a list of Omani tribes with there affiliation (Ibāḍī/Sunnī, Ghāfirī/Hināwī) and the regions where they are concentrated. The discussion in this note is taken largely from Peterson 1978, 112-114. The treatment there relies heavily on Wilkinson 1972a.
Keywords: Vie politique – Oman – 1970-2020

Democratic development in Oman - Jones, Jeremy; Ridout, Nicholas Peter (Middle East Journal, 2005)
Keywords: Vie politique – Oman – 1970-2020

The Ṣuḥār Paradox: Social and Political Mobilisations in the Sultanate of Oman since 2011 - Valeri, Marc (Chroniques yéménites, 2015)
Les mouvements de revendication politique et sociale qui ont agité le sultanat d’Oman en 2011 et 2012 sont les plus importants que le pays ait connus depuis la fin de la guerre du Dhofar dans les années 1970. Le fait que les manifestations les plus sérieuses soient survenues dans la ville de Ṣuḥār, au riche passé commercial, semble paradoxal. Laissée-pour-compte de la modernisation centralisatrice mise en œuvre par l’État après 1970, la ville avait vu l’implantation du port industriel à la fin des années 1990, qui se voulait la vitrine internationale de la diversification économique du pays, comme une aubaine. Cet article replace les manifestations qui se sont déroulées à Ṣuḥār dans la perspective de la transformation fulgurante, en l’espace de quelques années, de cette petite ville de province en capitale industrielle du pays. Plus largement l’étude du cas de Ṣuḥār permet de se pencher sur les racines socio-économiques du « printemps omanais » de 2011, ainsi que sur les réponses apportées par le régime à un mouvement populaire qu’il n’avait pas anticipé et porteur de conséquences majeures à long terme pour la légitimité du régime.
Keywords: Vie politique – Oman – 1970-2020

Chronologie des événements en Oman en 2006 - Valeri, Marc (Chroniques yéménites, 2007)
Keywords: Vie politique – Oman – 1970-2020

Something Stirring under the Still Waters of Oman: Tightening the Grip or Revitalizing the Monarchy? - Valeri, Marc (Chroniques yéménites, 2007)
Keywords: Vie politique – Oman – 1970-2020

Réveil laborieux pour l'Etat-Qabous : Identité nationale et légitimité politique dans l'Oman d'aujourd'hui - Valeri, Marc (Maghreb-Machrek, 2003)
Keywords: Vie politique – Oman – 1970-2020

Démocratiser les pétromonarchies du Golfe? Le cas du sultanat d'Oman - Mayol, Clémence (Esprit, 2005)
La guerre américaine en Irak est, nous dit-on, à l'origine d'un grand nombre de processus de démocratisation en cours, d'Égypte en Arabie Saoudite. L'analyse précise des réformes en cours dans le sultanat d'Oman invite à relativiser cette vision quelque peu irénique pour ne pas se laisser prendre aux mirages des « démocraties sans démocrates ».
Keywords: Vie politique – Oman – 1970-2020

Au milieu des convulsions régionales: Lente démocratisation à Oman - Callies de Salies, Bruno (Le Monde diplomatique, 2004)
Depuis de longues années, Oman se conduit comme l’un des principaux alliés de l’Occident dans la région du Golfe persique et a appuyé l’intervention en Afghanistan. En revanche, il s’est opposé publiquement à l’attaque des Etats-Unis contre l’Irak. Washington prétend, à travers ce conflit, obliger le monde arabe à adopter le modèle démocratique occidental. L’exemple d’Oman prouve précisément qu’il s’agit d’une tâche ardue, qui ne peut être improvisée, et encore moins imposée, depuis l’étranger.
Keywords: Vie politique – Oman – 1970-2020

Le débat sur l'identité nationale en Oman : rapport de consultance rédigé pour la Délégation aux affaires stratégiques (Ministère de la Défense, 2004)
Ce travail s'attache à mettre en évidence, dans un contexte historique, les ressorts de la remarquable stabilité du sultanat d'Oman depuis 1970, date à laquelle le sultan Qabous Bin Sa'id a accédé au trône. Héritier d'un territoire sans Etat, le nouveau souverain, porté au pouvoir par les britanniques, a su construire durant son règne une identité nationale omanaise moderne et associer l'image de sa personne au développement économique et social sans précédent impulsé par l'Etat et la rente pétrolière. Pourtant, loin de se révéler en rupture avec l'histoire moderne d'Oman, comme le suggère l'historiographie officielle, le règne de Qabous s'inscrit par de nombreux aspects dans la continuité du règne de son père, Sa'id (1932-1970). En mêlant cooptation des élites traditionnelles et coercition à l'égard des foyers de contre-pouvoirs, le souverain a rallié à son autorité l'ensemble des forces sociopolitiques susceptibles de le gêner. La dernière décennie a [vu] néanmoins de nombreux bouleversements se produire dans la société omanaise, avec l'apparition de défis politiques et sociaux à même de remettre en cause la stabilité en place : ralentissement de la production pétrolière, revendications politiques inédites, nécessaire nationalisation des emplois, etc. L'une des principales évolutions consiste en une repolarisation de la société autour d'identités infra-nationales - ethnolinguistiques, régionales - anciennes ou nouvelles.
Keywords: Vie politique – Oman – 1970-2020

Oman's insurgencies: the sultanate's struggle for supremacy - Peterson, John E. (Saqi, 2007)
Keywords: Vie politique – Oman – 1970-2020

L’Édification de l’État en Oman depuis 1970 - Peterson, John E. (L'Oman contemporain: État, territoire, identité, 2002)
Keywords: Vie politique – Oman – 1970-2020

L’Odyssée de l’Oman: de l’Imamat au Sultanat - Peterson, John E. (L'Oman contemporain: État, territoire, identité, 2002)
Keywords: Vie politique – Oman – 1970-2020

Les étapes de la construction juridique et judiciaire du Sultanat d’Oman - Da Lage, Olivier (L'Oman contemporain: État, territoire, identité, 2002)
Keywords: Vie politique – Oman – 1970-2020

L'Oman contemporain: État, territoire, identité - Lavergne, Marc; Dumortier, Brigitte (Karthala, 2002)
Keywords: Vie politique – Oman – 1970-2020

The Omani Pursuit of a Large Peninsula Shield Force: A Case Study of a Small State's Search for Security - Mason, Robert (British Journal of Middle Eastern Studies, 2014)
After the failure of a small Peninsula Shield Force (PSF) to protect Kuwait in the lead up to the Gulf War in 1991, Sultan Qaboos, the ruler of Oman, proposed to the Gulf Cooperation Council (GCC) that it develop a large-standing army of 100,000 troops. Although Oman was not wholly successful in achieving its objective during the main negotiation period up to 1995, it did manage to contribute to small shifts in GCC security policy during periods of conﬂict. Nevertheless, it took the Arab Uprisings in 2011 to achieve a fundamental re-orientation of GCC security policy which favoured higher numbers of PSF troops. This paper analyses the factors which facilitated and constrained Omani policy during the 20-year period and argues that Oman is only able to further its security interests when they are framed in a way that are conducive to the overriding political interests of the GCC.
Keywords: Vie politique – Oman – 1970-2020

The emergence of states in a tribal society: Oman under Saʻid bin Taymur, 1932-1970 - Rabi, Uzi (Sussex Academic Press, 2006)
Keywords: Vie politique – Oman – 1970-2020

A modern history of Oman: formation of the state since 1920 - Owtram, Francis (I.B. Tauris, 2004)
Keywords: Vie politique – Oman – 1913-1932; Vie politique – Oman – 1932-1970; Vie politique – Oman – 1970-2020

Majlis al-Shura in Oman - Salimi, Hussain S. al- (Modern Oman: studies on politics, economy, environment and culture of the Sultanate, 2006)
Keywords: Vie politique – Oman – 1970-2020

Broadening political participation in Oman. Basic facts - Kapiszewski, Andrzej (Modern Oman: studies on politics, economy, environment and culture of the Sultanate, 2006)
Keywords: Vie politique – Oman – 1970-2020

Oman under Qaboos: the emergence of a new diplomatic style in the Gulf - Rabi, Uzi (Modern Oman: studies on politics, economy, environment and culture of the Sultanate, 2006)
Keywords: Vie politique – Oman – 1970-2020

Modern Oman: studies on politics, economy, environment and culture of the Sultanate - Kapiszewski, Andrzej; Salimi, Abdulrahman al-; Pikulski, Andrzej (Księgarnia Akademicka, 2006)
Keywords: Vie politique – Oman – 1970-2020

Oman Under Qaboos: From Coup to Constitution, 1970-1996. - Allen, Jr, Calvin H.; Rigsbee II, W. Lynn (Frank Cass, 2000)
This is an examination of the political, economic and social development of Oman from the accession Sultan Qaboos in a palace coup in 1970 to the promulation of the basic law of 1996. The book argues that the sultanate does not follow the ""rentier"" model but the patriarchal tradition.
Keywords: Vie politique – Oman – 1970-2020

The Ibadhi Imamate of Muhammad bin ‘Abdallah al-Khalili (1920–54): The Last Chapter of a Lost and Forgotten Legacy - Rabi, Uzi (Middle Eastern Studies, 2008)
Keywords: Vie politique – Oman – 1970-2020; Vie politique – Oman – 20e siècle

Majlis al-Shura and Majlis al-Dawla: Weaving Old Practices and New Realities in the Process of State Formation in Oman - Rabi, Uzi (Middle Eastern Studies, 2002)
Keywords: Vie politique – Oman – 1970-2020

Oman under Qabus: From Coup to Constitution, 1970-1996 by Calvin Allen, Jr.; W. Lynn Rigsbee, II - Rabi, Uzi (Middle Eastern Studies, 2001)
Keywords: Recension; Vie politique – Oman – 1970-2020

Oman and the Arab–Israeli Conflict: The Reflection of a Pragmatic Foreign Policy - Rabi, Uzi (Israel Affairs, 2005)
The foreign policy of the Sultanate of Oman has differed markedly from those of other Arab Gulf countries, let alone other Arab states. Many a time, governments and political leaders throughout the region have been bewildered by Muscat’s nonconformist stance. Perhaps nowhere was the independence of Oman’s foreign policy more evident than in its attitude toward Israel and the Arab-Israeli conﬂict. The focus of this article is Oman’s policy toward the Arab-Israeli conﬂict from 1970 to the present day. In arguing that it is just another component of the country’s multifaceted foreign policy, the discussion traces Oman’s political history and offers insights into how this foreign policy has been shaped. It identiﬁes the logic behind Oman’s policy initiatives, and assesses its ability to adapt to changing regional and international environments.
Keywords: Vie politique – Oman – 1970-2020

Oman's Foreign Policy in the Twenty-First Century - Lefebvre, Jeffrey A. (Middle East Policy, 2010)
Keywords: Vie politique – Oman – 1970-2020

A reformer on the throne: Sultan Qaboos bin Said Al Said - Plekhanov, Sergeĭ (Trident Press Ltd, 2004)
Keywords: Vie politique – Oman – 1970-2020

Subjects of Stability: Understanding the stability of the Qaboos regime through the views and experiences of Omani students - Tersmette, Keye Simon (Leiden University, 2014)
Keywords: Vie politique – Oman – 1970-2020

Oman's Diverse Society: Northern Oman - Peterson, John E. (Middle East Journal, 2004)
Although the majority of Oman's population is Arab and either Ibadi or Sunni Muslim, the country exhibits a wealth of diversity in ethnic groups and native languages. While these other groups are often small in total size, they are represented in such areas as politics and commerce in numbers disproportionate to the weight of their communities and, although distinctive, are more or less woven into the social fabric of the country. Ethnic identity seems likely to decline as the various communities increasingly mix in education, the workplace, residential areas, social functions, the military, and elsewhere. This article provides brief “snapshots” of these groups and assesses their changing status in Omani society.
Keywords: Vie politique – Oman – 1970-2020

Legislation and legitimation in Oman: the Basic Law - Siegfried, Nikolaus (Islamic Law and Society, 2000)
When Sultan Qabus issued Decree 101 on November 6, 1996, Oman was the last Arab country to implement a constitutional document. However, the political impact of this document is controversial: Whereas some consider the Basic Law a step towards democratization, others see merely a continuation of traditional policies. In this article I investigate the innovative potential of the Basic Law. Against the background of Omani and regional history and European and Islamic constitutional thought, I review the Decree with regard to authority and legitimation. I suggest that the law is mainly symbolic in character. It exploits tribal and Islamic concepts to create a historically unfounded notion of a homogeneous state. The civil liberties it grants do not extend to the public sphere. I conclude that Oman's Basic Law does nothing more than to freeze the status quo, according to which the Sultan remains the only recognized authority in the state.
Keywords: Vie politique – Oman – 1970-2020

His Majesty Sultan Qaboos as a Paradigm of Peace: Images in Foreign Writings and Media - Hajri, Hilal al-; Panagiotou, Nikolas S. (Oman, Ibadism and modernity, 2018)
Keywords: Vie politique – Oman – 1970-2020

Oman and the Arab Spring: A Counterpoint to the Image of the Disintegrating Middle Eastern State - Rabi, Uzi (Today's perspectives on Ibadi history, 2017)
Keywords: Vie politique – Oman – 1970-2020

Ibadism and Omani Nation-Building since 1970 - Valeri, Marc (On Ibadism, 2014)
Keywords: Vie politique – Oman – 1970-2020

A Political Culture and Foreign Policy Shaped by a Moderate Religious View: The Case of the Sultanate of Oman - Rabi, Uzi (Oman and overseas, 2013)
Keywords: Vie politique – Oman – 1970-2020

Oman Reborn: Balancing Tradition and Modernization - Funsch, Linda Pappas (Palgrave Macmillan, 2015)
The Sultanate of Oman is one of the few "good news" stories to have emerged from the Middle East in recent memory. This book traces the narrative of a little-known and relatively stable Arab country whose history of independence, legacy of interaction with diverse cultures, and enlightened modern leadership have transformed it in less than fifty years from an isolated medieval-style potentate to a stable, dynamic, and largely optimistic country.At the heart of this fascinating story is Oman’s sultan, Qaboos bin Sa’id, friend to both East and West, whose unique leadership style has resulted in both domestic and foreign policy achievements during more than four decades in office.Exploring Oman from a historical perspective, Funsch examines how the country’s unique blend of tradition and modernization has enabled it to succeed while others in the region have failed. Accounts of the author’s own experiences with Oman’s transformation add rich layers of depth, texture, and personality to the narrative.
Keywords: Vie politique – Oman – 1970-2020